Tourists’ visitation intention to Pangkor island in Malaysia, a behavioural study - Ng, Ker Nie; Thong, Mei Xin (2023)
Tourism involves multidisciplinary industries. Therefore, tourists’ spending creates additional job employment opportunities and extra income for local and adjacent residents. Pangkor Island is self-sufficient in supporting tourism businesses and yet, the number of tourists arriving has been dropping since 2018. Therefore, it is essential to understand consumer behaviour so that policymakers can reform their tourism planning appropriately. This project targets the Gen-Z potential tourists who reside in Malaysia because they are the biggest tourist market segment in Malaysia and the tourist attractiveness in Pangkor Island can meet their social, relaxation, enjoyment, recreation, education, and learning expectations. To solve problems elicited in the preliminary study, the TPB model is modified by incorporating an additional variable, electronic word-of-mouth (ewom). Such a conceptual framework fills the knowledge gaps and several literature gaps. First, the application of TPB in tourism studies that examine the island tourism destination is not been published in Web of Science (wos) and Scopus-indexed journals, Secondly, the current research model decomposes a TPB’s predictor, perceived behavioural control into a two-dimensional variable: self-efficacy and facilitating conditions (FC). Thirdly, this project targets a niche market segment because every market segment has its own behavioural pattern. Quantitative data is collected from 345 respondents. To ensure the data is valid, the questionnaire item statements were screened through two processes: pre- and pilot tests. To ensure the data is reliable and represents the target population’s behaviour, a series of statistical analyses were undertaken. The results show that all the TPB variables create significant effects and ewom is not significant. Discussion pertaining the support and non-support of hypothesis is presented so that appropriate implications to policymakers and academics can be recommended. The project’s limitations and appropriate recommendations to future researchers are presented as well.